ALMEIDA, S. Racismo estrutural. São Paulo: Pólen, 2019. 264 p. ISBN 978-85-98349-75-6. - Chinatti Yamanaka, Juliana Harumi (Bakhtiniana. Revista de Estudos do Discurso, 2021)
Resenha: ALMEIDA, S. Racismo estrutural. São Paulo: Pólen, 2019. 264 p. ISBN 978-85-98349-75-6.